1983
DOI: 10.1111/j.1469-7998.1983.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and effect of intracellular rickettsia‐ like micro‐ organisms infecting second‐ stage juveniles of the Potato cyst‐ nematode Globodera rostocbiensis

Abstract: For the first time rickettsia‐like micro‐organisms are illustrated infecting most tissues of second‐stage juveniles of Globoderu rostochiensis. They were seen only inside host cells, except for the few degenerating forms in the intestinal lumen. They were most common in the non‐contractile (sarcoplasmic) region of body wall muscles. A study of the oesophageal glands of the nematode suggested that micro‐organisms present within these glands would be unlikely to pass out of them and that the nematode would not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…This gene is located directly adjacent to the phage-like putative protein translocation system (PLTS) along with numerous ATP-/transport-related genes, suggesting possible coordination of fatty-acid metabolic activities. This result is consistent with previous experiments implicating Cardinium in nematode lipid metabolism in the juvenile infective stage ( Walsh et al, 1983b ). Recent transcriptome analysis ( Gardner et al, 2018 ) support ATP-binding and transport as important functions in this Cardinium .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This gene is located directly adjacent to the phage-like putative protein translocation system (PLTS) along with numerous ATP-/transport-related genes, suggesting possible coordination of fatty-acid metabolic activities. This result is consistent with previous experiments implicating Cardinium in nematode lipid metabolism in the juvenile infective stage ( Walsh et al, 1983b ). Recent transcriptome analysis ( Gardner et al, 2018 ) support ATP-binding and transport as important functions in this Cardinium .…”
Section: Discussionsupporting
confidence: 94%
“…For Wolbachia , PCR prevalence data showed that about half of the P. penetrans individuals analyzed were infected, indicating a non-obligate association and potentially imperfect vertical transmission in P. penetrans , contrasting with data previously reported for wRad in R. similis ( Haegeman et al, 2009 ). The tissue distribution of Cardinium in P. penetrans matched that reported from cyst nematodes G. rostochiensis, H. goettingiana, H. avenae , and H. glycines ( Shepherd et al, 1973 ; Endo, 1979 ; Walsh et al, 1983a , b ; Noel and Atibalentja, 2006 ; Yang et al, 2017 ), with presence throughout the tissues of the nematode body including the ovary walls and oocytes, although it was unclear whether cPpe occupied the esophageal glands. In contrast to wPpe, PCR showed cPpe to be at nearly 100% prevalence in this P. penetrans population, consistent with data from Heterodera spp.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations